2009
DOI: 10.1111/j.1471-3802.2009.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and disengagement: exploring the disjuncture between SEN policy and practice

Abstract: Special Educational Needs (SEN) policy and practice in England and Wales currently relies on an authoritative and accurate diagnosis of need by professionals working in partnership with parents and children. Our analysis suggests there is a ‘continuum of disengagement’ for children and young people with SEN. This will be used as a central theme to illustrate the disjuncture between SEN policy and practice. The continuum becomes apparent under the scrutiny of issues that arise during the diagnostic process. Ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Second, studies of several different groups (e.g., children with ASD or ADHD) have consistently shown an association between parental depression and concern about their child (Karp, Ibañez, Warren, & Stone, ). Third, peer problems are often a key reason for referring children for SEND evaluation (McKay & Neal, ), such that ratings from nursery staff who have ample opportunities to observe children interacting with their peers may prove very useful.…”
Section: Introductionmentioning
confidence: 99%
“…Second, studies of several different groups (e.g., children with ASD or ADHD) have consistently shown an association between parental depression and concern about their child (Karp, Ibañez, Warren, & Stone, ). Third, peer problems are often a key reason for referring children for SEND evaluation (McKay & Neal, ), such that ratings from nursery staff who have ample opportunities to observe children interacting with their peers may prove very useful.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies were concerned with school engagement or social engagement (e.g. McKay and Neal 2009;Travell and Visser 2006). Very few studies examined academic engagement from a perspective that was similar to the US construct that was examined in this review.…”
Section: Selection Criteriamentioning
confidence: 97%
“…Riddick () counters the medicalisation of dyslexia, suggesting that the location of all dyslexic difficulties within individuals is a potential cause of oppression. Other conceptualisations of dyslexia view it as socially defined, through references to cultural and social norms (McKay & Neal, ). MacDonald () considers dyslexia bio‐socially, accepting the existence of underlying impairments but emphasising the need to consider the effects of social structures on the manifestation and mediation of ‘symptoms’ of dyslexia.…”
Section: Introductionmentioning
confidence: 99%
“…Riddick (), McKay and Neal () and later Ross () have suggested that some individuals with dyslexia may be legally disabled under the Equality Act 2010 (s6 (1)), according to which an individual is disabled if: (a)‘P[erson] has a physical or mental impairment, and (b)the impairment has a substantial and long‐term adverse effect on P’s ability to carry out normal day‐to‐day activities.’ …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation